A Diagnostic Dilemma: Job Syndrome Mimics Abusive Trauma - Serbülent Kılıç; Arzu Oto; Orhan Görükmez; Ayşenur Metin (Galenos Yayinevi, 2024)
In some cases, making of physical abuse diagnosis can be difficult if the findings were derived from an unusual disease or an unexpected finding of a common disease. A female infant was admitted to emergency department of our hospital, who was suffering from loss of consciousness. Examination and imaging methods revealed subarachnoid hemorrhage, old and new femur fractures, bilateral retinal hemorrhage. Performing genetic tests with multidisciplinary approach concluded that our case was found to have a mutation, DOCK8 (NM_001190458; c.2071G>A; p.Val691Met), suggests to Job syndrome (JS). JS is not only an immunodeficiency syndrome but also can be manifested by skeletal and connective tissue disorders. The fractures were most likely due to JS. Physicians must be aware of these probabilities. On the other hand, though it was only reported in a heterozygous form in GenomAD (genome aggregation database) it has big value that it was homozygous in our case.